Recycling of Ceramic Tiles and Marble Powder waste as Partial Substitution in Concrete - Bilawal Soomro; Sajjad Ali Mangi; Rashid Ali Bajkani; Abdul Qudoos Junejo (Neutron, 2021)
Recycling the waste has been one of the most influential aspect affecting global conditions of the world. In the world of Civil Engineering, it serves the purpose of preservation of the natural building materials such as Sand, Stones, etc. Fair amount of work been done on utilization of the waste such as Fly ash, marble waste, tiles waste, plastic, etc. used as different forms of replacement, provokes the need of work still to be done. So much of the work has been done on wastes available from Marble and Tiles. The combined effect of waste marble powder (M.P) and Ceramic tile waste (CTW) as partial replacement of Cement (10%) and Coarse Aggregates (10%,20%,30% respectively) is to be observed and analyzed. The obtained results will be compared with the conventional cement concrete at 7 and 28 days of Curing. Total 24 number of cylinders casted and tested for their workability and Compressive strength. The Workability of Concrete with replacement decreased with increasing ratio of replacement as well as its Compressive Strength. The Compressive strength of concrete with replacement is approximately of same value as that of Conventional Concrete at (10%+10%) partial substitution ratio.